2017
DOI: 10.20944/preprints201701.0049.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Discrimination and Distress among Afghan Refugees in Northern California: The Moderating Role of Pre- and Post-Migration Factors

Abstract: This study investigates the effect of perceived discrimination on the mental health of Afghan refugees, and secondly, tests the distress moderating effects of pre-migration traumatic experiences and post-resettlement adjustment factors. In a cross-sectional design, 259 Afghans completed surveys assessing perceived discrimination and a number of other factors using scales developed through inductive techniques. Multivariate analyses consisted of a series of hierarchical regressions testing the effect of perceiv… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The adaptation of Afghans in the U.S. has also included significant stigmatisation targeting their Muslim religious identities which has grown and become more politicised in recent years. Levels of perceived discrimination are high among first and second generation Afghans, but we did not find research exploring how much this has influenced their economic integration (Alemi and Stempel 2018). ACS has no measures of perceived discrimination, but we hypothesise that a substantial part of the much stronger negative Afghan refugee effects in Model 4 (−19%) stems from discrimination.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…The adaptation of Afghans in the U.S. has also included significant stigmatisation targeting their Muslim religious identities which has grown and become more politicised in recent years. Levels of perceived discrimination are high among first and second generation Afghans, but we did not find research exploring how much this has influenced their economic integration (Alemi and Stempel 2018). ACS has no measures of perceived discrimination, but we hypothesise that a substantial part of the much stronger negative Afghan refugee effects in Model 4 (−19%) stems from discrimination.…”
Section: Discussionmentioning
confidence: 83%
“…Regarding exposure to trauma, the modest mediating role of the crude index of physical and mental disability on the negative effect of Afghan refugees on earned income would likely be larger with better measures of psychological distress. A community survey of Afghan refugees in northern California (Stempel 2009) found that among working age adults an index measuring symptoms of distress was negatively associated with being employed, controlling for age, gender, education, English ability, and years in the U.S. Alemi and Stempel (2018) found that Afghan refugees who had experienced more traumatic events before and during migration had distress levels that were strongly influenced by their levels of perceived discrimination. Future work should explore more closely how this interaction between vulnerability from traumatic experiences and perceived discrimination influences economic outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation